Developing Android Based Interactive Learning Media To Master Grammar Skill At SMKN Campalagian - Nurul Syafika (Journal of Research Education and English Teaching, 2025)
This study aims to produce an android-based media and improve the understanding of Grammar students in the English language. This type of research is research and development which refers to the 4D development model: definition, design, development, and Disseminate. The purpose of R&D development is to produce application products and verify the effectiveness of learning videos, identify the need to develop products, and validate products that meet the requirements, and criteria for effectiveness and efficiency. The subjects of this study were Class X TO and Class X TJKT SMKN Campalagian. This research uses questionnaire instruments, namely (1) a media expert validation sheet to measure the feasibility of media, (2) a material validation sheet to measure the feasibility of media, (3) a student response questionnaire to determine the response of students to the attractiveness of the media developed. The findings showed that the process of creating Android-based interactive learning media had reached the define stage, which included front-end, student, concept, task, and learning objective formulation. This included creating learning materials, choosing media, and creating an initial design. Develop which consists of testing the feasibility/validity of product revisions, trials, and initial designs, and disseminate which consists of the influence of Android application-based learning media on improving student grammar skills. and Learning media declared effective based on the results of data analysis, Researcher found that there is an effect or there is a significant increase. The average value of the post-test experimental class is 83.13 while the value of the post-test Control class is 63.30. Successfully developed products can be implicated in any school.